Canine mammary minute oncocytomas with neuroendocrine differentiation associated with multifocal acinar cell oncocytic metaplasia. (November 2016) - Nagahara, Rei; Kimura, Masayuki; Itahashi, Megu; Sugahara, Go; Kawashima, Masashi; Murayama, Hirotada; Yoshida, Toshinori; Shibutani, Makoto
Two solitary and minute tumors of 1 and 1.5 mm diameter were identified by microscopy in the left fourth mammary gland of a 13-year-old female Labrador Retriever dog, in addition to multiple mammary gland tumors. The former tumors were well circumscribed and were composed of small-to-large polyhedral neoplastic oncocytes with finely granular eosinophilic cytoplasm, and were arranged in solid nests separated by fine fibrovascular septa. Scattered lumina of variable sizes containing eosinophilic secretory material were evident. Cellular atypia was minimal, and no mitotic figures were visible. One tumor had several oncocytic cellular foci revealing cellular transition, with perivascular pseudorosettes consisting of columnar epithelial cells surrounding the fine vasculature. Scattered foci of mammary acinar cell hyperplasia showing oncocytic metaplasia were also observed. Immunohistochemically, the cytoplasm of neoplastic cells of the 2 microtumors showed diffuse immunoreactivity to anti-cytokeratin antibody AE1/AE3, and finely granular immunoreactivity for 60-kDa heat shock protein, mitochondrial membrane ATP synthase complex V beta subunit, and chromogranin A. One tumor also had oncocytic cellular foci forming perivascular pseudorosettes showing cellular membrane immunoreactivity for neural cell adhesion molecule. The tumors were negative for smooth muscle actin, neuron-specific enolase, vimentin, desmin, S100, and synaptophysin. Ultrastructural observation confirmed the abundant mitochondria in the cytoplasm of both neoplastic and hyperplastic cells, the former cells also having neuroendocrine granule–like electron-dense bodies. From these results, our case was diagnosed with mammary oncocytomas accompanied by neuroendocrine differentiation. Scattered foci of mammary oncocytosis might be related to the multicentric occurrence of these oncocytomas.